Light-dependent expression of four cryptic archaeal circadian gene homologs - Maniscalco, Michael; Nannen, Jennifer; Sodi, Valerie; Silver, Gillian; Lowrey, Phillip; Bidle, Kelly (Frontiers in Microbiology, 2014)
Circadian rhythms are important biological signals that have been found in almost all major groups of life from bacteria to man, yet it remains unclear if any members of the second major prokaryotic domain of life, the Archaea, also possess a biological clock. As an initial investigation of this question, we examined the regulation of four cyanobacterial-like circadian gene homologs present in the genome of the haloarchaeon Haloferax volcanii. These genes, designated cirA, cirB, cirC, and cirD, display similarity to the KaiC-family of cyanobacterial clock proteins, which act to regulate rhythmic gene expression and to control the timing of cell division. Quantitative RT-PCR analysis was used to examine the expression of each of the four cir genes in response to 12 h light/12 h dark cycles (LD 12:12) in H. volcanii during balanced growth. Our data reveal that there is an approximately two to sixteen-fold increase in cir gene expression when cells are shifted from light to constant darkness, and this pattern of gene expression oscillates with the light conditions in a rhythmic manner. Targeted single- and double-gene knockouts in the H. volcanii cir genes result in disruption of light-dependent, rhythmic gene expression, although it does not lead to any significant effect on growth under these conditions. Restoration of light-dependent, rhythmic gene expression was demonstrated by introducing, in trans, a wild-type copy of individual cir genes into knockout strains. These results are noteworthy as this is the first attempt to characterize the transcriptional expression and regulation of the ubiquitous kaiC homologs found among archaeal genomes.